Ansätze zur Entwicklung eines neuen Vollgenossenschaftsmodells mit integrierter Währung Ein Vorschlag für eine wirkungsvolle Genossenschaftsform mit Beiträgen zu einer gemeinwohlorientierten Wirtschaftslehre - Martignoni, Jens (Gemeinwirtschaft und Gemeinwohl I Social Economy and Common Welfare, 2022)
This transdisciplinary work develops a new business model for cooperatives: The full cooperative, which enables a regionally based, sustainable, climate-friendly and peaceful way of doing business and living. The basic principles are derived from the ideal image and practice of historical full cooperatives. Taking into account organisational theory, system theory and monetary theories, a new organisational form is outlined that could develop greater resilience in the preservation and implementation of cooperative values and goals. The model involves a consistent merging of production and consumption, uses an internal monetary system and calls for extensive participation of its members.